Molding resin material and its manufacturing method

By mixing powdered cellulose with thermoplastic resins and a thermoplastic elastomer, and then heating and kneading the mixture, the challenges of hydrophilic issues and increased costs in wood-based biomass and polypropylene molding are addressed, resulting in a stable, carbon-neutral molding resin material with improved moldability.

JP7655823B2Active Publication Date: 2025-04-02NIPPON PAPER IND CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021142153
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-09-01
Publication Date
2025-04-02
Estimated Expiration
2041-09-01

AI Technical Summary

Technical Problem

Existing methods for mixing wood-based biomass with polypropylene for molding result in hydrophilic issues, surface irregularities, and increased costs due to the need for additional polymer compounds.

Method used

A molding resin material is developed by combining powdered cellulose with thermoplastic resins like polypropylene and polyethylene, along with a thermoplastic elastomer, and heating and kneading the mixture to achieve uniformity and improved moldability.

Benefits of technology

The solution stabilizes the production of a highly viscous molding resin material that avoids cutting or cracking during injection molding, while also enhancing carbon neutrality by increasing the powdered cellulose content.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007655823000001
    Figure 0007655823000001
Patent Text Reader

Abstract

To provide a resin material for molding which is formed by uniformly mixing powdery cellulose and a thermoplastic resin, has such has viscosity as to prevent cutting and breakage in injection molding, and facilitates molding.SOLUTION: A resin material for molding contains 40-90 mass% of powdery cellulose having an average particle diameter of 100 μm or less, and further contains a thermoplastic resin and a thermoplastic elastomer (preferably, styrene-butadiene-based block copolymer, ethylene-octene-based copolymer, and propylene-ethylene-based copolymer).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a molding resin material containing powdered cellulose, a thermoplastic resin such as polypropylene, polyethylene, polylactic acid, and the like, and a thermoplastic elastomer, and a method for producing the same. [Background technology]

[0002] Biomass materials are attracting attention as industrial resources. Biomass materials are materials derived from plants and other living organisms. Because biomass materials are organic, they emit carbon dioxide when burned. However, the carbon contained in them comes from carbon dioxide absorbed from the atmosphere by the biomass through photosynthesis during its growth, so it is safe to say that the use of biomass materials does not increase the amount of carbon dioxide in the atmosphere overall. This property is called carbon neutral.

[0003] Against the backdrop of global warming and other global environmental issues, there is an urgent need to conserve resources, recycle waste materials to turn them into raw materials, and promote environmental circulation, as typified by biodegradable plastics. In Japan, the revised Recycling Law and the Green Purchasing Law have been established, and the need for products that comply with these laws is also on the rise.

[0004] In this situation, blending biomass materials into resin molded products, which are widely used from materials for automobile parts to everyday items, will promote the practice of the carbon neutral concept. For example, Patent Document 1 describes a composite material containing carboxylmethylated cellulose nanofibers, a polymer compound having a primary amino group, an acid-modified polyolefin, and a polyolefin. Patent Document 2 describes a cellulose composite material containing wood pulp and a polymer matrix. Patent Document 3 describes a method of mixing wood flour and random polypropylene resin and manufacturing a wood flour-containing resin injection molded product using an injection molding machine. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. WO2014 / 087767 [Patent Document 2] Special Publication No. 2019-512591 [Patent Document 3] JP 2010-138337 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, when simply mixing "wood-based biomass" and "polypropylene," heating and melting them, and molding them, problems arose, such as the fact that the wood-based biomass is hydrophilic and therefore cannot be mixed uniformly with the polypropylene, the resin body being cut into small pieces at the outlet of the device that injects the mixture of wood-based biomass and polypropylene, and the surface of the resulting molded article not being smooth.

[0007] For example, Patent Document 1 describes the use of carboxymethylated cellulose nanofibers, but in order to carboxymethylate the cellulose and further increase the uniform dispersion with the polyolefin resin, it is necessary to add a polymer compound having a primary amino group and an acid-modified polyolefin, which increases costs.

[0008] Therefore, an object of the present invention is to provide a molding resin material mixed with wood-based biomass, in which wood-based biomass and thermoplastic resin are uniformly mixed and which is less susceptible to cutting or cracking during molding, such as injection, at low cost. [Means for solving the problem]

[0009] The present inventors discovered that a molding resin material with excellent moldability can be obtained by mixing powdered cellulose, a thermoplastic resin such as polypropylene, polyethylene, or polylactic acid, and a thermoplastic elastomer, and then heating and kneading the mixture, and thus completed the present invention.

[0010] The present invention includes, but is not limited to, the following: (1) A molding resin material containing 40 to 90 mass % of powdered cellulose having an average particle size of 100 μm or less, and further containing a thermoplastic resin and a thermoplastic elastomer. (2) The molding resin material according to (1), wherein the thermoplastic elastomer is any one of a styrene-butadiene block copolymer, an ethylene-octene copolymer, and a propylene-ethylene copolymer. (3) The molding resin material according to (1) or (2), wherein the blending ratio of the powdery cellulose, the thermoplastic resin, and the thermoplastic elastomer is 40-90:59-10:1-20. (4) The molding resin material according to any one of (1) to (3), which contains 0.1 to 15 mass % of maleic anhydride-modified polypropylene as a compatibilizer. (5) The molding resin material according to any one of (1) to (4), wherein the thermoplastic resin comprises a polyolefin resin. (6) The molding resin material according to any one of (1) to (5), wherein the thermoplastic resin comprises a polyethylene resin. (7) The molding resin material according to any one of (1) to (6), wherein the thermoplastic resin contains a biodegradable resin. (8) A method for producing a molding resin material, comprising the step of heating and kneading powdered cellulose, a thermoplastic resin, and a thermoplastic elastomer. (9) The method according to (8), wherein in the heating and kneading step, the molding material is continuously produced by processing with a twin-screw kneading extruder. Effect of the Invention

[0011] According to the present invention, it is possible to stably produce a molding resin material containing powdered cellulose that is highly viscous and does not break or crack during injection molding. In addition, by increasing the blending ratio of powdered cellulose, it is possible to obtain a molding resin material that is excellent in carbon neutrality. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The powdered cellulose used in the present invention can be obtained by pulverizing a cellulose raw material such as pulp that has been subjected to acid hydrolysis with a mineral acid (i.e., an inorganic acid) such as hydrochloric acid, sulfuric acid, nitric acid, etc., or by mechanically pulverizing a cellulose raw material such as pulp that has not been subjected to acid hydrolysis. Note that the powdered cellulose used in the present invention is preferably a powdered cellulose with few impurities that has been pulverized from a cellulose raw material such as pulp that has been subjected to acid hydrolysis.

[0013] In the present invention, the pulp, which is the cellulose raw material used as the raw material, is preferably pulp derived from wood. Examples of pulp derived from wood include pulp derived from broadleaf trees and pulp derived from conifers, and chemical pulp derived from broadleaf trees is particularly preferred. The pulping method (cooking method) of these wood-derived chemical pulps is not particularly limited, and examples include sulfite cooking, kraft cooking, soda-quinone cooking, and organosolv cooking. Among these, sulfite cooking and kraft cooking are preferred. Examples of chemical pulp include kraft pulp (KP), dissolving kraft pulp (DKP), sulfite pulp (SP), and dissolving sulfite pulp (DSP). Both unbleached and bleached chemical pulp can be used as the chemical pulp. Examples of other chemical pulps include groundwood pulp (GP), refiner groundwood pulp (RGP), thermomechanical pulp (TMP), and chemi-thermomechanical pulp (CTMP). As the mechanical pulp, mechanical pulp such as groundwood pulp (GP), refiner groundwood pulp (RGP), thermomechanical pulp (TMP), and chemi-thermomechanical pulp (CTMP) can be used.

[0014] The pulping process (cooking process) dissolves and removes the coloring substance lignin in the pulp, resulting in whitening. To further increase the whiteness of the pulp, a bleaching process can be carried out. There is no particular limitation on the bleaching process method, and any commonly used method can be used. For example, pulp delignified by any conventional method can be subjected to a combination of chlorine treatment (C), chlorine dioxide bleaching (D), alkaline extraction (E), hypochlorite bleaching (H), hydrogen peroxide bleaching (P), alkaline hydrogen peroxide treatment stage (Ep), alkaline hydrogen peroxide-oxygen treatment stage (Eop), ozone treatment (Z), chelate treatment (Q), etc., in the sequence DE / PD, C / DEHD, ZED-PZ / D-Ep-D, Z / D-Ep-DP, D-Ep-D, D-Ep-DP, D-Ep-PD, Z-Eop-DD, Z / D-Eop-D, Z / D-Eop-DED, etc. (" / " in the sequence means that the treatment before and after " / " are performed consecutively without washing). The brightness of the pulp as a cellulose raw material is preferably 80% or more based on ISO 2470.

[0015] The method for producing powdery cellulose of the present invention will be exemplified below.

[0016] Powdered cellulose is manufactured through the processes of raw pulp slurry preparation, acid hydrolysis reaction, neutralization, washing and deliquation, drying, pulverization and classification.

[0017] More specifically, the process is as follows. The raw pulp slurry preparation process is a process of preparing a raw pulp slurry using a cellulose raw material. The acid hydrolysis reaction process is a process of hydrolyzing the raw pulp slurry with an acid concentration of 0.10 to 1.0N to prepare a hydrolysate. The neutralization, washing, and deliquor process is a process of neutralizing the hydrolysate, washing it, and then deliquoring it. The drying process is a process of drying the deliquored hydrolysate to obtain a dried product. The classification process is a process of pulverizing the dried product to obtain a pulverized product. Through these processes, the cellulose powder of the present invention can be produced.

[0018] The pulp that can be used in the method for producing powdered cellulose of the present invention can be in a fluidized state or in a sheet state. When fluidized pulp from a pulp bleaching process is used as the raw material, it is necessary to increase the concentration before feeding into the hydrolysis reaction tank, and a predetermined amount is fed into the reaction tank after concentrating it with a dehydrator such as a screw press or a belt filter. When a dry sheet of pulp is used as the raw material, the pulp is loosened with a crusher such as a roll crusher and then fed into the reaction tank.

[0019] Next, the dispersion liquid with a pulp concentration of 3 to 10% by weight (solid content equivalent) adjusted to an acid concentration of 0.1 to 30% by weight is subjected to acid hydrolysis under the conditions of a reaction temperature of 80 to 100°C and a reaction time of 30 minutes to 3 hours. The hydrolyzed pulp is neutralized by adding an alkaline agent and washed. Then, in the deliquor process, the hydrolyzed pulp and the waste acid are separated into solid and liquid. The hydrolyzed pulp is dried in a dryer and mechanically crushed and classified to a specified size in a crusher. Note that after neutralization, washing, and deliquor, the solid content concentration may be adjusted by dehydration before drying. By adjusting the solid content concentration before drying, it becomes easier to control the physical properties of the powdered cellulose.

[0020] Examples of the pulverizer used in the method for producing powdery cellulose of the present invention include the following.

[0021] Cutting type mills: mesh mills (manufactured by Horai Co., Ltd.), Atoms (manufactured by Yamamoto Hyakuma Manufacturing Co., Ltd.), knife mills (manufactured by Palman), cutter mills (manufactured by Tokyo Atomizer Manufacturing Co., Ltd.), CS cutters (manufactured by Mitsui Mining Co., Ltd.), rotary cutter mills (manufactured by Nara Machinery Works, Ltd.), turbo cutters (manufactured by Freund Corporation), pulp crushers (manufactured by Zuiko Co., Ltd.), and shredders (manufactured by Kobe Steel Pantech Co., Ltd.), etc.

[0022] Hammer mill: Jaw crusher (manufactured by Makino Corporation) and hammer crusher (manufactured by Makino Sangyo Co., Ltd.).

[0023] Impact mills: Pulverizer (manufactured by Hosokawa Micron Corporation), Fine Impact Mill (manufactured by Hosokawa Micron Corporation), Super Micron Mill (manufactured by Hosokawa Micron Corporation), Innomizer (manufactured by Hosokawa Micron Corporation), Fine Mill (manufactured by Nippon Pneumatic Mfg. Co., Ltd.), CUM type centrifugal mill (manufactured by Mitsui Mining Co., Ltd.), Exceed Mill (manufactured by Makino Sangyo Co., Ltd.), Ultraplex (manufactured by Makino Sangyo Co., Ltd.), Contraplex (manufactured by Makino Sangyo Co., Ltd.), Coroplex (manufactured by Makino Sangyo Co., Ltd.), Sample Mill (manufactured by Seishin Co., Ltd.), Bantam Mill (manufactured by Seishin Co., Ltd.), Atomizer (manufactured by Seishin Co., Ltd.), Tornado Mill (manufactured by Nikkiso Co., Ltd.), Nea Mill (manufactured by Dalton Co., Ltd.), HT type fine grinding mill (manufactured by Horai Co., Ltd.), Free grinding mill (manufactured by Nara Machinery Works Co., Ltd.), New Cosmomizer (manufactured by Nara Machinery Works Co., Ltd.), Turbo Mill (manufactured by Freund Corporation), Gather Mill (manufactured by Nishimura Machinery Works Co., Ltd.), Super Powder Mill (manufactured by Nishimura Machinery Works Co., Ltd.), Blade Mill (manufactured by Nisshin Engineering Inc.), Super Rotor (manufactured by Nisshin Engineering Inc.), Npa Crusher (manufactured by Sansho Industry Co., Ltd.), Wheeley grinding mill (manufactured by Sanki Manufacturing Co., Ltd.), Pulp grinding machine (manufactured by Zuikou Co., Ltd.), Jacobson fine grinding mill (manufactured by Kobe Steel Pantech Co., Ltd.), and Universal Mill (manufactured by Tokuju Machinery Works Co., Ltd.).

[0024] Airflow mills: CGS type jet mill (manufactured by Mitsui Mining Co., Ltd.), Micron Jet (manufactured by Hosokawa Micron Corporation), Counter Jet Mill (manufactured by Hosokawa Micron Corporation), Cross Jet Mill (manufactured by Kurimoto Iron Works, Ltd.), Supersonic Jet Mill (manufactured by Japan Pneumatic Mfg. Co., Ltd.), Current Jet (manufactured by Nisshin Engineering Inc.), Jet Mill (manufactured by Sansho Industry Co., Ltd.), Ebara Jet Micronizer (manufactured by Ebara Corporation), Ebara Triad Jet (manufactured by Ebara Corporation), Selenium Mirror (manufactured by Masuko Sangyo Co., Ltd.), New Micro Sictomat (manufactured by Masuno Manufacturing Co., Ltd.), and Kryptron (manufactured by Kawasaki Heavy Industries, Ltd.).

[0025] Vertical roller mills: Vertical roller mill (manufactured by Sinion Co., Ltd.), vertical roller mill (manufactured by Schaeffler Japan Co., Ltd.), roller mill (manufactured by Kotobuki Giken Kogyo Co., Ltd.), VX mill (Kurimoto Iron Works Co., Ltd.), KVM type vertical mill (Earth Technica Co., Ltd.), and IS mill (IHI Plant Engineering Co., Ltd.).

[0026] Of these, it is preferable to use a jaw crusher (manufactured by Makino Corporation), a pulverizer (manufactured by Hosokawa Micron Corporation), a super micron mill (manufactured by Hosokawa Micron Corporation), a tornado mill (manufactured by Nikkiso Co., Ltd.), a free grinding machine (manufactured by Nara Machine Works, Ltd.), a turbo mill (manufactured by Freund Corporation), a super powder mill (manufactured by Nishimura Machine Works, Ltd.), a blade mill (manufactured by Nisshin Engineering Inc.), a supersonic jet mill (manufactured by Japan Pneumatic Mfg. Co., Ltd.), or a current jet (manufactured by Nisshin Engineering Inc.), which have excellent fine grinding properties.

[0027] In the present invention, the pulp may be pulverized in two stages. For example, powdery cellulose can be produced by a method including a first pulverization step in which the pulp is pulverized to obtain a pulverized product having an average particle size of 100 μm or less, followed by a second pulverization step in which the pulverized product obtained in the first pulverization step is further pulverized to obtain a pulverized product having an average particle size of 50 μm or less.

[0028] For the purpose of imparting or improving functionality to the powdered cellulose of the present invention, it is possible to mix one or more types of the powdered cellulose raw material with other organic and / or inorganic components in any ratio and pulverize them. In addition, it is possible to perform chemical treatment within a range that does not significantly impair the degree of polymerization of the cellulose raw material used as the raw material.

[0029] The average particle size of the powdered cellulose of the present invention is preferably 100 μm or less, more preferably 50 μm or less. If the average particle size of the powdered cellulose is larger than 100 μm, it becomes difficult to mix it uniformly with the resin, and problems such as the resin being cut into small pieces at the outlet of the device that injects the mixture of the pulverized material and the resin, and the difficulty of conveying it to the cooling treatment device may occur.

[0030] The average particle size is the 50% volume average particle size (D50) measured by laser light scattering (laser diffraction) and can be measured using a laser diffraction / scattering particle size distribution analyzer (Malvern, device name: Mastersizer 2000) or the like.

[0031] The apparent specific gravity of the powdered cellulose of the present invention is preferably 0.30 g / ml or more, more preferably 0.33 g / ml or more, and the upper limit is preferably 0.60 g / ml or less, more preferably 0.50 g / ml or less, and even more preferably 0.45 g / ml or less.

[0032] In this specification, the apparent specific gravity is a value calculated by putting 10 g of a sample into a 100 ml measuring cylinder, tapping the bottom of the measuring cylinder until the height of the sample stops decreasing (manually for approximately 10 minutes), and reading the scale on the flat surface.

[0033] The molding resin material of the present invention can be obtained by heating and kneading the above powdery cellulose, thermoplastic resin, and thermoplastic elastomer. The compounding ratio of the roasted material in the molding resin material is preferably high in order to achieve a high level of carbon neutrality, but is preferably 40% by mass or more and 90% by mass or less, more preferably 50% by mass or more and 80% by mass or less, in consideration of the production and strength of the resulting resin material and molded article.

[0034] The thermoplastic resin used in the present invention is preferably molded into granules for ease of handling, but may be in any form. Two or more types of thermoplastic resins may be used simultaneously.

[0035] Examples of thermoplastic resins include, but are not limited to, polyethylene and polypropylene, and any resin that can be plasticized and molded by heat can be used. Among them, polyethylene such as LDPE (low density polyethylene) and polypropylene are preferred from the viewpoint of moldability.

[0036] In the present invention, a biodegradable resin may be used as the thermoplastic resin. Examples of the biodegradable resin having thermoplasticity include, but are not limited to, polylactic acid (PLA), polybutylene succinate, polyethylene succinate, polyglycol, polycaprolactone, polyvinyl alcohol, and the like.

[0037] Furthermore, when kneading with powdery cellulose, a compatibilizing resin (compatibilizing agent) which is also a thermoplastic resin may be added for the purpose of improving uniformity and adhesion.

[0038] As the compatibilizing resin, a known one can be used, and examples thereof include, but are not limited to, maleic anhydride modified polypropylene (UMEX 1010, manufactured by Sanyo Chemical Industry Co., Ltd.) and Modic (registered trademark) P908 (manufactured by Mitsubishi Chemical Industry Co., Ltd.). The compatibilizing resin acts to improve the uniform mixing and adhesion between the roasted product and the thermoplastic resin. The compatibilizing resin does not have to be used, but when used, it is preferably used in an amount of 0.1 to 15 mass %, more preferably 0.5 to 10 mass %, in the molding resin material obtained by kneading.

[0039] In the present invention, by adding a thermoplastic elastomer, it is possible to stably produce a molding resin material with high viscosity that does not cut, crack, or the like during injection molding, even when ground wood biomass roasted material is blended.

[0040] The thermoplastic elastomer used in the present invention may be a styrene-based thermoplastic elastomer. More specifically, it may be a block copolymer such as a styrene-butadiene-styrene (SBS) copolymer, a styrene-isoprene-styrene (SIS) copolymer, a styrene-ethylene-butylene-styrene (SEBS) copolymer, a styrene-ethylene-propylene-styrene (SEPS) copolymer, or a styrene-butadiene-butylene-styrene (SBBS) copolymer. These may be used alone or in combination of two or more.

[0041] The thermoplastic elastomer used in the present invention may be a polyolefin-based elastomer. More specifically, it may be an ethylene-butene copolymer, EPR (ethylene-propylene copolymer), modified ethylene-butene copolymer, EEA (ethylene-ethyl acrylate copolymer), modified EEA, modified EPR, modified EPDM (ethylene-propylene-diene terpolymer), ionomer, α-olefin copolymer, modified IR (isoprene rubber), modified SEBS (styrene-ethylene-butylene-styrene copolymer), halogenated isobutylene-paramethylstyrene copolymer, ethylene-acrylic acid modified product, ethylene-vinyl acetate copolymer, and acid modified product thereof, and mixtures containing them as main components. These may be used alone or in combination of two or more.

[0042] Preferred thermoplastic elastomers for use in the present invention include styrene-butadiene block copolymers, ethylene-octene copolymers, propylene-ethylene copolymers, etc. Styrene-butadiene block copolymers are particularly preferred. The above thermoplastic elastomers may be modified with maleic anhydride, fumaric anhydride, etc. In the styrene-butadiene block copolymers, the styrene content is preferably 15 to 30% by mass.

[0043] The blending ratio of the thermoplastic elastomer is preferably 1 to 20 mass%, and more preferably 3 to 10 mass%. That is, the blending ratio of the pulverized wood biomass roasted material, the thermoplastic resin, and the thermoplastic elastomer is preferably 40-90:59-10:1-20.

[0044] A molded article can be obtained by heat-treating the molding resin material of the present invention. The temperature at which the molding resin material of the present invention is heat-treated (heated, melted, kneaded, etc.) is usually about 100 to 300° C., preferably about 110 to 250° C., and particularly preferably about 120 to 220° C. The molded article obtained by heat treatment can be molded into a desired shape by a conventionally known resin molding method.

[0045] In the method for producing a molding resin material of the present invention, the roasted product and the thermoplastic resin can be heated and kneaded using an apparatus generally used in resin molding. For example, a general extruder or a twin-screw kneading extruder can be used. The TEX series manufactured by Japan Steel Works can be used as the twin-screw kneading extruder.

[0046] The molding resin material of the present invention can be used to produce various molded articles. For molding, a method commonly used for molding thermoplastic resins can be used, such as, but not limited to, injection molding, extrusion molding, blow molding, mold molding, hollow molding, and foam molding.

[0047] The molding resin material of the present invention or the molded article obtained by molding it may contain organic and / or inorganic substances other than the thermoplastic resin and the roasted product. Examples of other components include alkalis such as sodium hydroxide, potassium hydroxide, magnesium hydroxide, calcium hydroxide, etc.; inorganic fillers such as clay, talc, calcium carbonate, myca, titanium dioxide, zinc oxide, etc.; organic fillers such as carbon black, graphite, glass flakes, etc.; dyes or pigments such as red iron oxide, azo pigments, phthalocyanines, etc.; and additives for modification such as dispersants, lubricants, plasticizers, release agents, flame retardants, antioxidants (phenolic antioxidants, phosphorus antioxidants, sulfur antioxidants), antistatic agents, light stabilizers, ultraviolet absorbers, metal deactivators, crystallization promoters (nucleating agents), foaming agents, crosslinking agents, and antibacterial agents.

[0048] The molding resin material of the present invention can be molded for various purposes and can be used as a substitute for plastic products. Molded articles obtained from the molding resin material of the present invention can be widely applied to, for example, trays, automobile parts, interiors such as automobile dashboards, luggage compartments for airplanes, structural members for transport equipment, housings for home appliances, electrical appliance members, cards, various containers such as toner containers, building materials, seedling pots, agricultural sheets, writing implements, wooden products, household appliances, straws, cups, toys, sports goods, port members, building members, generator members, tools, fishing gear, packaging materials, 3D printer models, pallets, food containers, tableware, cutlery (spoons, forks, etc.), chopsticks, various sheets, etc. When these products are no longer needed, they will be disposed of, but even if they are incinerated and carbon dioxide is emitted, the powdered cellulose contained therein can be treated as not increasing the amount of carbon dioxide in the atmosphere. EXAMPLES

[0049] The present invention will be described in more detail below with reference to experimental examples of the present invention, but the present invention is not limited to these experimental examples. Unless otherwise specified, parts and % refer to parts by mass and % by mass, and numerical ranges are described as including their endpoints.

[0050] [Example 1] Cellulose powder (W-50GK, average particle size 47μm, Nippon Paper Industries Co., Ltd.), polyethylene (product name: Novatec HD HJ5800N, Japan Polyethylene Co., Ltd.), styrene-butadiene block copolymer as a thermoplastic elastomer (product name: Tuftec H1221, styrene content 12%, Asahi Kasei Co., Ltd.), and acid-modified polyolefin as a compatibilizer (product name: UMEX 1010, acid value 52, molecular weight 30000, Sanyo Chemical Industries Co., Ltd.) were mixed in a mixing ratio of 50:35:10:5, and the mixture was kneaded at 190℃ for 6 minutes in a DSM Xplore Compounder 15 (Leo Labs), molded at 190℃ in the heating barrel (9bar 2s-11bar 0.5s-11bar 24s), and molded at 40℃ to prepare a dumbbell of the molding resin material, and the physical properties were measured.

[0051] [Example 2] A molding resin material was produced in the same manner as in Example 1, except that a maleic anhydride-modified styrene-butadiene block copolymer (product name: M1943, styrene content 20%, manufactured by Asahi Kasei Corporation) was used as the thermoplastic elastomer.

[0052] [Example 3] A molding resin material was produced in the same manner as in Example 1, except that powdered cellulose (product name: W-50GK, particle size 54 μm, manufactured by Nippon Paper Industries Co., Ltd.), LLDPE as a thermoplastic resin (product name: Novatec LL UJ890, manufactured by Japan Polyethylene Corporation), styrene-butadiene block copolymer as a thermoplastic elastomer (product name: Tuftec H1221, styrene content 12%, manufactured by Asahi Kasei Corporation), and acid-modified polyolefin as a compatibilizer (product name: UMEX 1010, manufactured by Sanyo Chemical Industries, Ltd.) were mixed in a blend ratio of 51:38.5:10:0.5.

[0053] [Comparative Example 1] A molding resin material was produced in the same manner as in Example 1, except that no thermoplastic elastomer was added, and powdered cellulose (W-50GK, average particle size 47 μm, manufactured by Nippon Paper Industries Co., Ltd.), polyethylene (product name: Novatec HD HJ5800N, manufactured by Japan Polyethylene Corporation), and an acid-modified polyolefin as a compatibilizer (product name: UMEX 1010, acid value 52, molecular weight 30,000, manufactured by Sanyo Chemical Industries, Ltd.) were mixed in a blend ratio of 50:45:5.

[0054] The tensile strength of the molding resin materials produced in Examples 1 to 3 and Comparative Example 1 was measured by the following method. The results are shown in Table 1. [Measurement of tensile strength]: JIS K 6251 dumbbells were created using a DSM Xplore Compounder 15 (manufactured by Leo Labs) and measured at a tensile speed of 1 mm / min in accordance with JIS K 7161: Plastics - Tensile properties test method.

[0055] [Table 1]

[0056] As shown in Table 1, the molding resin materials of Examples 1 to 3 to which a thermoplastic elastomer was added had higher breaking strain and higher tenacity than the molding resin material of Comparative Example 1 to which a thermoplastic elastomer was not added, and therefore were shown to have excellent moldability.

Claims

1. A molding resin material comprising: (a) powdered cellulose having an average particle size of 100 μm or less; (b) a thermoplastic resin; (c) a thermoplastic elastomer; and (d) maleic anhydride-modified polypropylene as a compatibilizer, The molding resin material described above, wherein the powdery cellulose content is 50 to 80% by mass, and the maleic anhydride-modified polypropylene content is 0.1 to 15% by mass.

2. 2. The molding resin material according to claim 1, wherein the thermoplastic elastomer is any one of a styrene-butadiene block copolymer, an ethylene-octene copolymer, and a propylene-ethylene copolymer.

3. 3. The molding resin material according to claim 1, wherein the blending ratio of the powdered cellulose, the thermoplastic resin, and the thermoplastic elastomer is 40-90:59-10:1-20.

4. A molding resin material described in any one of claims 1 to 3, wherein the content of maleic anhydride modified polypropylene is 0.5 to 10 mass %.

5. The molding resin material according to any one of claims 1 to 4, wherein the thermoplastic resin comprises a polyolefin-based resin.

6. The molding resin material according to any one of claims 1 to 5, wherein the thermoplastic resin comprises a polyethylene-based resin.

7. A molding resin material described in any one of claims 1 to 6, wherein the thermoplastic resin contains LDPE (low density polyethylene) and the thermoplastic elastomer contains a styrene-butadiene block copolymer.

8. A method for producing the molding resin material according to any one of claims 1 to 7, comprising the steps of: The above method further comprises a step of heating and kneading powdered cellulose, a thermoplastic resin, and a thermoplastic elastomer.

9. The method according to claim 8, wherein in the heating and kneading step, the molding resin material is continuously produced by treating at 120 to 220°C using a twin-screw kneading extruder.

Citation Information

Patent Citations

  • Method for producing molded article containing wood flour, and molded article

    JP2010138337A

  • Polypropylene composition and method for producing the same

    JP2011231237A

  • Thermoplastic resin composition in which amorphous cellulose is composited and production method thereof

    JP2015155535A

  • Exterior part for vehicle

    JP2019064403A

  • Resin composition

    JP2019199563A